THE MECHANISM OF MANAGEMENT BASED ON STAFFING IN PRESCHOOL EDUCATION ORGANIZATIONS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article analyzes the concept and characteristics of management "management" and the importance of result-based management in the management of preschool education.